Microbial Services for Cereal Crops: Reducing Costs and Environmental Impact - Rigobelo, Everlon Cid [UNESP] (Springer Nature, 2024)
This book will focus on microbial services as an excellent strategy to face the current challenge of global agriculture, collecting the principal studies that used microbial services for improving cereal production, such as rice, beans, maize and wheat. This book will address studies and discussion about the bacterial world inside the plant; phytostimulator microorganisms; promotion of maize growth for biocontrol; filamentous fungi as plant growth promoters; mycorrhiza; sustainable agriculture effects on the microbiome; humic substances in combination with plant growth-promoting bacteria in rice; and the changes in plant metabolome induced by microorganisms under environmental stress.
Keywords: Domesticated microbiome; Effect of transgenic plant on its microbiome; Effects of sustainable agriculture on the microbiome; Microbial Service; Microbiome management and engineering; Mushroom technology for biocontrol; Plant Growth-Promoting Rhizobacteria; Plant Growth-Promoting Rhizobacteria for cereal production; Soil Microbiology; Soil Microbiome